How general are general purpose technologies? Evidence from nano-, bio- and ICT-technologies in Finland - Tuomo Nikulainen; Martti Kulvik (The Research Institute of the Finnish Economy (ETLA), 2009)
General purpose technologies (GPT) have a significant impact on economic activity through radical technological change and wide technological diffusion. This paper aims to address the generality of technologies associated with the GPT concept. Information and communications technologies (ICT), biotechnology and nanotechnology are viewed as existing or potential general purpose technologies, but there is a lack of empirical evidence of their generality. This paper addresses the argument by using patent, industry and company level data from Finland. The results provide evidence that ICT, as expected, is a GPT. Nanotechnology shows signs of being potentially widely applicable, but for biotechnology the channels of technological diffusion seem to be fewer and more focused on areas where Finnish companies are less active. The results and discussion are also reflected on the newly formed innovation policy instrument in Finland - SHOKs (Strategic centres for science, technology and innovation), which aim to direct a large share of the Finnish public R&D subsidies towards more demand-based and incumbent- driven innovation activity.
Keywords: O30; O33; O38; 330; general purpose technology; technology diffusion; science-based technology; ICT; biotechnology; nanotechnology; SHOK; Informationstechnik; Biotechnologie; Nanotechnologie; Technischer Fortschritt; Innovationsdiffusion; Innovationspolitik; Finnland